2019
DOI: 10.4018/ijdldc.2019100101
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Digital Technologies on Learning Behavior and Reading Motivation Among Moroccan EFL University Students

Abstract: The introduction of digital technologies and the emergence of electronic reading devices have expanded the concept of literacy and shaped how readers consume information from texts, as well as how they perceive and interact with digital materials vs. print materials in academic settings. Several years ago, reading was merely a characteristic of print. However, with today's advances in technology, the vast majority of people are reading blogs, journals, newspapers, and other materials on digital screens. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
5
0
2
Order By: Relevance
“…Једно од новијих истраживања које је спроведено на узорку студената енглеског језика у Мароку (Larhmaid, Nour, & Afflerbach, 2019) дало је интересантан увид у разлоге коришћења е-књига у образовању. Наиме, налази овог истраживања сугеришу да је читање штампаних књига погодније када задатак читања укључује дуге текстове и захтева већу активност и ангажовање у учењу.…”
Section: електронске књиге у учењу страних језикаunclassified
See 1 more Smart Citation
“…Једно од новијих истраживања које је спроведено на узорку студената енглеског језика у Мароку (Larhmaid, Nour, & Afflerbach, 2019) дало је интересантан увид у разлоге коришћења е-књига у образовању. Наиме, налази овог истраживања сугеришу да је читање штампаних књига погодније када задатак читања укључује дуге текстове и захтева већу активност и ангажовање у учењу.…”
Section: електронске књиге у учењу страних језикаunclassified
“…Велики број ученика оценио је своје целокупно искуство читања на мрежи као задовољавајуће или угодно. Kao недостатке, студенти наводе напетост очију, нелагодност приликом читања на мрежи, као и веродостојност и квалитет текстова на мрежи као главнe изазовe и препреке при употреби дигиталних текстова (Larhmaid et al, 2019).…”
Section: електронске књиге у учењу страних језикаunclassified
“…The results support the multidimensional nature of L2 reading motivation and the importance of intrinsic motivation in explaining L2 reading motivation. Larhmaid, Nour, and Afflerbach (2019) reported that students' motivation to read online is driven by the need to keep up with recent information and use usability features embedded with etexts such as the 'Find' function and built-in annotation tools. A great number of students rated their overall online reading experience as satisfactory or enjoyable.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that students' online reading is a highly potent strategy in enhancing reading habits among students (Larhmaid et al, 2019;Rimi, 2019). Concerning gender and hours spent on online reading, males appeared to read more hours than females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation